Factors Influencing Pregnant Women’s Compliance With Tetanus Toxoid (Tt) Immunization In Jambi - Yoiko Suci Pyar Restu; Dwi Noerjoedianto; Budi Aswin; M. Ridwan; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the factors associated with pregnant mothers' compliance in implementing tetanus toxoid (TT) immunization at Puskesmas Talang Banjar, Jambi City. TT immunization is an important program to prevent tetanus in mothers and infants, but its coverage still faces challenges. This quantitative study with a cross-sectional design involved 90 pregnant mothers in the working area of Puskesmas Talang Banjar. Data were collected through questionnaires measuring knowledge, attitudes, education level, husband's support, healthcare provider's support, and pregnant mothers' compliance with TT immunization. The study results indicate that the majority of pregnant mothers have positive attitudes towards TT immunization (70%) and most receive good support from their husbands (66.7%) and healthcare providers (66.7%). However, the distribution of pregnant mothers' knowledge is evenly divided between low and high categories, with some areas of knowledge needing improvement, particularly regarding the benefits of TT immunization during pregnancy. Further analysis shows that positive attitudes, husband's support, and healthcare provider's support are correlated with pregnant mothers' compliance in implementing TT immunization. Nevertheless, a portion of respondents still exhibit negative attitudes, lack adequate support from their husbands, or receive low support from healthcare providers. This suggests the need for comprehensive educational and outreach efforts, as well as strengthening the roles of husbands and healthcare providers, to enhance pregnant mothers' awareness and compliance with TT immunization.